2014
DOI: 10.5901/jesr.2014.v4n6p11
|View full text |Cite
|
Sign up to set email alerts
|

Re-Thinking the Value of Learning Theories to Develop Self-Directedness in Open-Distance Students

Abstract: Learning is a complex process that has generated numerous interpretations and theories as to how exactly it can be effectively facilitated to ensure that meaningful learning is achieved. This article will examine the value of different learning theories to develop self-directedness in Open distance learning students. While the basic assumptions and principles of social constructivism are not disputed, it is argued that we must be mindful not to replace one learning theory with yet another and promote a 'one si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…As Richards and Farrell (2016) noted, this theory is particularly relevant for beginner teachers facing challenging tasks. Geduld (2014) emphasises that the theory promotes collaborative learning and social interaction in developing self-directedness. Manning (2007) identifies SDL as a key element of adult learning theory, which includes various approaches like andragogy and experiential learning.…”
Section: Problem Statementmentioning
confidence: 99%
“…As Richards and Farrell (2016) noted, this theory is particularly relevant for beginner teachers facing challenging tasks. Geduld (2014) emphasises that the theory promotes collaborative learning and social interaction in developing self-directedness. Manning (2007) identifies SDL as a key element of adult learning theory, which includes various approaches like andragogy and experiential learning.…”
Section: Problem Statementmentioning
confidence: 99%
“…It is, however, important to note that other studies have found that, in addition to the above four factors, English language proficiency (for educational institutions in which English is the language of instruction) and technological skills can also impact the success of self-directed learning approaches (Geduld, 2014, 2019; Bharuthram and Kies, 2013). This, in turn, can impact on learner satisfaction and engagement with an e-learning resource.…”
Section: Affordances Of Self-directed and Autonomous Learningmentioning
confidence: 99%
“…Students understood that they would 'do their own research', 'take responsibility for their own learning', improve their time management skills and 'learn to utilise technology better to support learning' as part of self-directed learning in blended learning. These students' comprehension of what self-directed earning entails aligns well with Geduld's (2014:16) description of self-directed learning, namely that such students can identify their own learning needs, are motivated by internal factors (such as their own learning needs and interests) and are actively engaged in interaction between lecturers and other students. Therefore, despite the fact that no emphasis was placed on self-directed learning as such in the blended module, the students had a good grasp of what it entails.…”
Section: Sub-theme 11: Students' Comprehension Of What Selfdirected mentioning
confidence: 99%